"It Feels Like You Have Stepped Back in Time": Implementing Authenticity Research in Henry VIII's Kitchens at Hampton Court Palace. Issue 1 (March 2020) - Peirce, Aileen; Jackson, Dan; Fitch, Richard; Manning, Aaron
In 2015, Historic Royal Palaces undertook a large-scale audience research study to explore how visitors to our sites understand the idea of authenticity and whether it matters. The key finding was that while visitors strongly agreed that historic building fabric and objects are important, their primary response to authenticity is emotional. Whether a space feels authentic is not simply about the material originality of the building and objects. Re-creations, human, and multisensory experiences were often seen as adding to authenticity. This research is informing and shaping Historic Royal Palaces's work, most notably the re-presentation of Henry VIII's Kitchens at Hampton Court Palace which opened in May 2018, combining historic building fabric and fixtures, re-created furniture and objects, groundbreaking use of audiovisuals (AV), and live interpretation led by our team of food historians. Taking Henry VIII's Kitchens as a case study, this article will reveal Historic Royal Palaces's research into visitor perceptions of authenticity and how this is being applied in practice.